POTENSI ANTAGONIS Bacillus sp ASAL KEBUN RAYA LIWA (KRL) SEBAGAI AGEN PENGENDALI JAMUR Fusarium sp - Indriani Indriani; Christina Nugroho Ekowati; Kusuma Handayani; Bambang Irawan (UIN Sunan Gunung Djati Bandung, 2023)
Fusarium sp is a type of fungus that is pathogenic especially on plants. This fungus attacks the pith tissue of the stem through the injured root. Yellow leaf color is an early indication of this fungal infection. An alternative in controlling this fungus could be to use Bacillus sp because these bacteria have growth inhibitory compounds. This study aims to determine the effect of Bacillus sp from Liwa Botanical Garden on Fusarium sp. Antagonist testing using dual culture method on media Mueller Hinton Agar (MHA) with 3 bacterial isolates was tested. The results of the antagonist test showed that the isolate Bacillus sp.TSR 6 had an inhibitory capacity of 19.7 mm with a strong inhibitory category against the fungus Fusarium sp.